Der Ramsey-Psalter: Commentary/Kommentar. Lucy Freeman Sandler - Kauffmann, M (University of Chicago Press, 2003)
Lucy Freeman Sandler, Der Ramsey-Psalter: Commentary/Kommentar. Dual-language text (English-German). (Codices Selecti, Phototypice Impressi, Commentarium 103*.) Graz: Akademische Druck- u. Verlagsanstalt, 1999. Pp. 343; 52 black-and-white figures, black-and-white diagrams, and tables.